2000
DOI: 10.22260/isarc2000/0066
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Highway Bridge Performance by Artificial Neural Networks and Genetic Algorithms

Abstract: Bridge management systems (BMS) comprise various techniques need to help make decisions on the type of works that need to be performed to maintain the serviceability of a bridge and to extend its useful life. These decisions rely on current and future bridge conditions therefore it is essential for a BMS to accurately predict the future bridge performance, or in other words to assess the extent of bridge deterioration. Numerous deterioration models are reported in the literature. Most of these methods were dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Therefore, using the same input data from a different bridge network could produce very different results. Tokdemir et al [29] compared artificial neural networks and genetic algorithms in predicting bridge sufficiency ratings. This paper concluded that the genetic algorithms outperformed the artificial neural networks, however, the one disadvantage of the use of genetic algorithms is the lengthy training times required.…”
Section: Artifical Intelligence (Ai) Machine Learning and Data Mininmentioning
confidence: 99%
“…Therefore, using the same input data from a different bridge network could produce very different results. Tokdemir et al [29] compared artificial neural networks and genetic algorithms in predicting bridge sufficiency ratings. This paper concluded that the genetic algorithms outperformed the artificial neural networks, however, the one disadvantage of the use of genetic algorithms is the lengthy training times required.…”
Section: Artifical Intelligence (Ai) Machine Learning and Data Mininmentioning
confidence: 99%
“…A multilayer ANN is used to relate the condition of the bridge superstructure to the number of years of service of the bridge and other relevant inputs. Tokdemir et al (2000) use ANN to forecast the bridge condition as a function of bridge geometry, level of traffic, years in service, and structural attributes as explanatory variables.…”
Section: Bridge Deterioration Modelingmentioning
confidence: 99%
“…The ANN technique was used to model bridge deterioration by relating age to the condition rating of the bridge superstructure (22). A detailed investigation was also carried out using ANN to predict bridge sufficiency ratings by incorporating age, geometry, and traffic attributes as explanatory variables (23). Although the ANN system is automated and utilizes a polynomial that best fits the data, it still has problems similar to the deterministic models.…”
Section: Artificial Intelligence Modelsmentioning
confidence: 99%